DEMOGRAPHIC PROCESSES IN THE REPUBLIC OF KARAKALPAKSTAN (TAMADDUN NURI JURNALI, 2025)
The article discusses the history of the formation of the multinational population in the Republic of Karakalpakstan, the history of friendly relations between the peoples living in this region, demographic indicators of the multinational population during the years of independence, and migration processes.